Convergence of Accounting Standards Does Not Always Lead to Convergence of Accounting Practices: The Case of China - Olesen, Karin; Cheng, Fiona (Asian Journal of Business and Accounting, 2017)
This paper explores the extent to which the adoption of the 2006 Accounting Standards for Business Enterprises (ASBE) in China has resulted in a closer alignment of the Chinese Generally Accepted Accounting Practices (GAAP) with the International Financial Reporting Standards (IFRS). We examine the annual reports of forty seven (47) companies listed on the Shanghai and Shenzhen Stock Exchanges over a two year period between 2006 and 2007. We find that the gap in the profit and equity values between the IFRS and the Chinese GAAP shrunk in absolute terms and that differences between the two sets of accounts disappear following the introduction of the ASBE 2006. In addition, we examine the source of the continued differences between the IFRS and the Chinese GAAP values following the introduction of the 2006 ASBE. The results show that the differences still exist in respect of treatments of financial assets and liabilities, revaluation and depreciation of financial assets, business combinations and land use rights, because even though the companies employed the fair value method in their IFRS accounts, they chose to implement cost method for their accounts prepared under the Chinese GAAP. Our results show that the alignment of standards through convergence has not caused an alignment of practices. Keywords: Chinese GAAP, International financial reporting standards